Generalized Green’s functions for second-order discrete boundary-value problems with nonlocal boundary conditions - Paukštaitė, Gailė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2012)
In this paper, generalized Green’s functions for second-order discrete boundaryvalueproblems with nonlocal boundary conditions are investigated, where the necessaryand sufficient existence condition of discrete Green’s function is not satisfied and nonlocalboundary conditions are described by linear functionals.
Keywords: discrete boundary-value problem; generalized Green function; Moore–Penrose inverse; nonlocal boundary conditions